The importance of a picture archiving and communications system (PACS) manager for large-scale PACS installations...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Beird LC (Journal of Digital Imaging)
Installing a picture archiving and communication system (PACS) is a massive undertaking for any radiology department. Facilities making a successful transition to digital systems are finding that a PACS manager helps guide the way and offers a heightened return on the investment. The PACS manager fills a pivotal role in a multiyear, phased PACS installation. PACS managers navigate a facility through the complex sea of issues surrounding a PACS installation by coordinating the efforts of the vendor, radiology staff, hospital administration, and the information technology group. They are involved in the process from the purchase decision through the design and implementation phases. They can help administrators justify a PACS, purchase and shape the request for proposal (RFP) process before a vendor is even chosen. Once a supplier has been selected, the PACS manager works closely with the vendor and facility staff to determine the best equipment configuration for his or her facility, and makes certain that all deadlines are met during the planning and installation phase. The PACS manager also ensures that the infrastructure and backbone of the facility are ready for installation of the equipment. PACS managers also help the radiology staff gain acceptance of the technology by serving as teachers, troubleshooters, and the primary point-of-contact for all PACS issues. This session will demonstrate the value of a PACS manager, as well as point out ways to determine the manager's responsibilities. By the end of the session, participants will be able to describe the role of a PACS manager as it relates to departmental operation and in partnership with equipment vendors, justify a full-time position for a PACS manager, and identify the qualifications of candidates for the position of PACS manager. Copyright (c) 1999 by W.B. Saunders Company